Being Reformed today? - D.J. Smit (Acta Theologica)
The article addresses the question of what it means to be Reformed today by discussing the different terms in the theme – “Reformed,” “Today,” “Being” – as well as the importance of the question mark itself. It engages with important historical figures and documents (Calvin, Barth, Barmen) as well as more contemporary works and statements (Wolterstorff, Niebuhr, Leith, Gerrish, Plasger, Welker, Nimmo and Fergusson, Boesak, Botman, Belhar, Kitwe, Debrecen, Accra) on being Reformed. It concludes by raising three challenges to being Reformed today, namely whether it can find the necessary normativity to self-critically engage its own tradition, whether the deepest convictions and passions of the Reformed faith still make sense in the world today, and whether there is the will within the Reformed community to practise this kind of being in the world today.